2005
DOI: 10.1007/s10979-005-3401-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Risk Assessment Accuracy: Underestimating Women's Violence Potential.

Abstract: Understanding factors that contribute to mental health professionals' (MHPs') accuracy in assessing patients risk of violence can inform efforts to improve accuracy and to integrate risk assessment technology with practice. Based on a sample of 147 clinicians who assessed 680 patients in a psychiatric emergency room, this study investigates the influence of patient gender, MHP gender, and their potential interaction on MHPS' risk assessment accuracy. The results indicate that MHPs of both genders are particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…Underreporting inappropriate behaviour exhibited by female psychiatric patients has been noted regarding violence (Skeem et al, 2005) and female sexual expression is often overlooked with women repeatedly construed as vulnerable (Hughes & Hebb, 2005;. Skeem et al (2005) suggested that underreporting occurred because males are generally more overtly violent.…”
Section: Contextualisingmentioning
confidence: 99%
See 1 more Smart Citation
“…Underreporting inappropriate behaviour exhibited by female psychiatric patients has been noted regarding violence (Skeem et al, 2005) and female sexual expression is often overlooked with women repeatedly construed as vulnerable (Hughes & Hebb, 2005;. Skeem et al (2005) suggested that underreporting occurred because males are generally more overtly violent.…”
Section: Contextualisingmentioning
confidence: 99%
“…Skeem et al (2005) suggested that underreporting occurred because males are generally more overtly violent. Regarding ISB, data from the Hospital suggested that the majority of ISB recordings were malerelated, supporting Skeem et al (2005). However, the findings from this study suggest that mere frequency is not a complete explanation.…”
Section: Contextualisingmentioning
confidence: 99%
“…Predictions that a male would not be violent were correct 70% of the time, but for females, they were correct only 55% of the time. Skeem et al (2005) had 147 clinicians assess 680 patients in a psychiatric emergency room for risk of future violence. Mental health professionals of both genders were "particularly limited in their ability to assess female patients' risk of future violence" (p. 173).…”
Section: Beliefs About Gender and Violence Perpetrationmentioning
confidence: 99%
“…Further, in other institutional settings where personality disorder evaluations and violence risk assessments are common, women represent approximately 40% (civil hospitals) and 10% (forensic psychiatric hospitals) of the population. A growing literature suggests that female aggression among people with serious mental disorders (Hodgins, Mednick, Brennan, Schulsinger, & Engberg, 1996;Nicholls, Brink, Webster, & Martin, manuscript under review;Nicholls, Ogloff, & Douglas, 2004;Skeem et al, 2005;Stueve & Link, 1998;Swanson, Holzer, Ganju, & Jono, 1990) and intellectually impaired individuals (Crocker et al, in press;Hodgins, 1992) rivals, and sometimes surpasses, the prevalence rates and severity of aggression among their male counterparts. In the family violence field, removal of the ''cloak of secrecy'' (Steinmetz & Lucca, 1988, p. 233) reveals that men's and women's rates of perpetrating intimate partner abuse are roughly equal (Archer, 2000;Dutton & Nicholls, 2005;Nicholls & Dutton, 2001;Straus, 1999), despite contrary evidence derived from criminal databases and victim surveys.…”
Section: The Importance Of Studying Psychopathy In Femalesmentioning
confidence: 99%